Debunking the Myth of Value-Neutral Virginity: Toward Truth in Scientific Advertising - Mandel, David R.; Tetlock, Philip E. (Frontiers in Psychology, 2016)
The scientific community often portrays science as a value-neutral enterprise that crisply demarcates facts from personal value judgments. We argue that this depiction is unrealistic and important to correct because science serves an important knowledge generation function in all modern societies. Policymakers often turn to scientists for sound advice, and it is important for the wellbeing of societies that science delivers. Nevertheless, scientists are human beings and human beings find it difficult to separate the epistemic functions of their judgments (accuracy) from the social-economic functions (from career advancement to promoting moral-political causes that “feel self-evidently right”). Drawing on a pluralistic social functionalist framework that identifies five functionalist mindsets—people as intuitive scientists, economists, politicians, prosecutors, and theologians—we consider how these mindsets are likely to be expressed in the conduct of scientists. We also explore how the context of policymaker advising is likely to activate or de-activate scientists’ social functionalist mindsets. For instance, opportunities to advise policymakers can tempt scientists to promote their ideological beliefs and values, even if advising also brings with it additional accountability pressures. We end prescriptively with an appeal to scientists to be more circumspect in characterizing their objectivity and honesty and to reject idealized representations of scientific behaviour that inaccurately portray scientists as value-neutral virgins.